Teacher malaise and inclusion: a bibliographic review based on CAPES theses and dissertations (Research, Society and Development, 2021)
This article aims to analyze the works that investigate the relationship between teacher malaise and the inclusion of students as a target audience of special education. This was a qualitative research with state-of-the-art research elements that sought theses and dissertations within the CAPES theses and dissertations catalog that dealt with teacher malaise and the inclusion of students as a target audience of special education. The selected works were analyzed in order to show which methodologies and theoretical references were adopted, as well as four categories were created to analyze the results and discussions of the works: 1) poor working conditions; 2) anxieties and frustrations; 3) teacher training; 4) solution/answer given about the malaise. The categories showed elements of complaints related to working conditions, their respective backgrounds and the reasons for their suffering, in addition to the search for solutions and answers that would explain these sufferings. This article showed that there are still gaps in the scientific production on the topic of teacher malaise related to inclusion, as well as showing signs of weakness and inconsistency in teacher education regarding the inclusion of students with disabilities. It is considered with the analyzes that inclusive education needs to be resignified by teachers appropriating ties free from prejudice and narcissistic actions.